Genotype, mycorrhizae, and herbivory interact to shape strawberry plant functional traits - Whyle, Robert L.; Trowbridge, Amy M.; Jamieson, Mary A. (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) and herbivores are ubiquitous biotic agents affecting plant fitness. While individual effects of pairwise interactions have been well-studied, less is known about how species interactions above and belowground interact to influence phenotypic plasticity in plant functional traits, especially phytochemicals. We hypothesized that mycorrhizae would mitigate negative herbivore effects by enhancing plant physiology and reproductive traits. We expected genotypic variation would influence functional trait responses to these biotic agents. To test these hypotheses, we conducted a manipulative field-based experiment with three strawberry (Fragaria x ananassa) genotypes to evaluate plant phenotypic plasticity in multiple functional traits. We used a fully-crossed factorial design in which plants from each genotype were exposed to mycorrhizal inoculation, herbivory, and the combined factors to examine effects on plant growth, reproduction, and floral volatile organic compounds (VOCs). Genotype and herbivory were key determinants of phenotypic variation, especially for plant physiology, biomass allocation, and floral volatiles. Mycorrhizal inoculation increased total leaf area, but only in plants that received no herbivory, and also enhanced flower and fruit numbers across genotypes and herbivory treatments. Total fruit biomass increased for one genotype, with up to 30-40% higher overall yield depending on herbivory. Herbivory altered floral volatile profiles and increased total terpenoid emissions. The effects of biotic treatments, however, were less important than the overall influence of genotype on floral volatile composition and emissions. This study demonstrates how genotypic variation affects plant phenotypic plasticity to herbivory and mycorrhizae, playing a key role in shaping physiological and phytochemical traits that directly and indirectly influence productivity.